C++ FAQs, Second Edition - Cline, Marshall; Lomow, Greg; Girou, Mike (Addison-Wesley Professional, 1998)
In a concise and direct question-and-answer format, C++ FAQs, Second Edition brings you the most efficient solutions to more than four hundred of the practical programming challenges you face every day. Moderators of the on-line C++ FAQ at compilerlang.c++, Marshall Cline, Greg Lomow, and Mike Girou are familiar with C++ programmers' most pressing concerns. In this book, the authors concentrate on those issues most critical to the professional programmer's work, and they present more explanatory material and examples than is possible on-line. This book focuses on the effective use of C++, helping programmers avoid combining seemingly legal C++ constructs in incompatible ways. This second edition is completely up-to-date with the final ANSI/ISO C++ Standard. It covers some of the smaller syntax changes, such as "mutable"; more significant changes, such as RTTI and namespaces; and such major innovations as the C++ Standard Library, including the STL. In addition, this book discusses technologies such as Java, CORBA, COM/COM+, and ActiveX--and the relationship all of these have with C++. These new features and technologies are iconed to help you quickly find what is new and different in this edition. Each question-and-answer section contains an overview of the problem and solution, fuller explanations of concepts, directions for proper use of language features, guidelines for best practices and practices to avoid, and plenty of working, stand-alone examples. This edition is thoroughly cross-referenced and indexed for quick access. Get a value-added service! Try out all the examples from this book at www.codesaw.com. CodeSaw is a free online learning tool that allows you to experiment with live code from your book right in your browser. 0201309831B11102003.